The Effect of Promotion and Service Quality on Visitor Satisfaction at PT Jentera Media Citra (Case Study at the Mama Lemon 2025 Event in Medan City) - Tarigan, Irene Cindy Therecia; Haro, Jamardua (CV. Civiliza Publishing, 2025)
In the modern marketing world, promotional event activities are an effective strategy in increasing consumer engagement and satisfaction. This study aims to determine the influence of promotion and service quality on visitor satisfaction at the 2025 Mama Lemon Event organized by PT Jentera Media Citra in Medan City. This event was held in various strategic culinary locations with promotional strategies such as sample sharing, interactive quizzes, and publications through social media. Informative and attractive promotions, as well as friendly and responsive services, are expected to be able to provide a positive experience for visitors. This study uses a quantitative method with a survey approach and multiple linear regression analysis. The results of the study showed that partially, promotion and service quality had a significant effect on visitor satisfaction, with a significance value of 0.001 each. Simultaneously, both variables were also shown to have a significant effect on satisfaction, with an F value of 13.378 and an R Square of 0.216, which means that 21.6% of the variation in visitor satisfaction was explained by promotion and quality of service